Left ventricular systolic function assessed by standard and advanced echocardiographic techniques in patients with systemic lupus erythematosus: A systemic review and meta-analysis - Maka Gegenava; Zviad Kirtava; William KF Kong; Tea Gegenava (Archives of Rheumatology, 2024)
Objectives: Aim of the study was to perform a systemic review and meta-analysis of the current case-control studies based on the assessment of the left ventricular (LV) systolic function with standard and advanced echocardiographic methods. Materials and methods: Objectives of the study, methods of statisticalanalysis, literature search strategy, inclusion andexclusion criteria, and outcome measurementswere defined according to Cochrane Collaborationsteps, 13 including recommendations for metaanalysisof observational studies in epidemiology (MOOSE). Results: A total of 850 papers were collected. Of those, eight papers (10 groups) including 174,442 SLE patients and 45,608,723 controls with heart failure (HF), 20 papers including 1,121 SLE patients and 1,010 controls with an evaluated LV ejection fraction (LVEF), and eight studies (nine groups) including 462 SLE patients and 356 controls with a measured LV global longitudinal strain (LVGLS) met the predefined inclusion criteria. HF rate in SLE patients was 2.39% (4,176 of 174,442 patients with HF), and SLE patients showed a 3.4 times higher risk for HF compared to controls. SLE patients had a lower LVEF compared to controls. LVGLS was more impaired in SLE patients compared to controls, irrespective of two-dimensional or three-dimensional speckle tracking echocardiography. Conclusion: Heart failure rate in SLE patients is high, and SLE patients showed a 3.4 times higher risk in patients with SLE compared to controls. LV systolic function, as measured by LVEF and LVGLS, is significantly affected in SLE patients, and LVGLS potentially represents a new tool for the early assessment of LV function.